2003
DOI: 10.1088/0953-2048/16/7/310
|View full text |Cite
|
Sign up to set email alerts
|

Defect structures in MgB2wires introduced by hot isostatic pressing

Abstract: The microstructures of MgB 2 wires prepared by the powder-in-tube technique and subsequent hot isostatic pressing were investigated using transmission electron microscopy. Large amount of crystalline defects including small angle twisting, tilting, and bending boundaries, in which high densities of dislocations reside, were found forming sub-grains within MgB 2 grains. It is believed that these defects resulted from particle deformation during the hot isostatic pressing process and are effective flux pinning c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…There have been numerous reports of the synthesis of bulk MgB 2 via sintering, and a number of studies have shown that high pressure and elevated temperature [15,16] are effective in promoting MgB 2 phase formation and subsequent sintering. The use of high-pressure leads typically to the introduction of defects in the MgB 2 structure that form effective pinning centres [17].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous reports of the synthesis of bulk MgB 2 via sintering, and a number of studies have shown that high pressure and elevated temperature [15,16] are effective in promoting MgB 2 phase formation and subsequent sintering. The use of high-pressure leads typically to the introduction of defects in the MgB 2 structure that form effective pinning centres [17].…”
Section: Introductionmentioning
confidence: 99%
“…The simulations in this paper are all processed via Large-scale Atomic/Molecular Massively Parallel Simulator code developed by Sandia National Laboratory, which has been extensively used to calculate Single crystal nickel nanowire in tensile test all kinds of properties of materials [13][14][15]. We choose embedded-atom method potential to describe the interaction between atoms in this paper, which is one of the most popular interatomic potentials for materials, especially for metallic materials [16].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies show that the hot isostatic pressing (HIP) process yielded MgB 2 superconducting material with smaller grains and higher density of connections between grains [14][15][16]. The HIP process increases the homogeneity and density of dislocations [17,18]. It leads to an increase in critical current density (J c ) and irreversibility field (B irr ) [19].…”
Section: Methodsmentioning
confidence: 99%